Gendered perceptions of biosecurity and the gender division of labor in pig farming in Uganda - Dioney, Michel; Ochago, Robert; Birungi, Rosemirta; Ouma, Emily; Lule, Peter; Kakinda, Mary Jo; Nyapendi, Robinah; Birungi, Rosemirta; Pyburnx, Rhiannon (Journal of Gender, Agriculture and Food Security, 2020)
African swine fever (ASF) is a highly infectious and lethal transboundary swine disease, which has devastating effects on the industry, especially in sub-Saharan Africa. Given the absence of a vaccine or effective treatment, on-farm biosecurity measures are the only means of controlling it. Women and men are both involved in pig farming but the implications of the gender division of labor in relation to ASF biosecurity measures have, until now, been unexplored. We use the Gender Dimension Framework to investigate the gender division of labor in pig farming, as well as gendered perceptions of biosecurity. Findings include that typical gender roles and the perceptions of men and women towards biosecurity undermine effective implementation of biosecurity measures. The paper contributes to a better understanding of the gendered dimension of ASF control. This knowledge will serve to improve ASF control measures and support better management of the disease, both during outbreaks and to effectively prevent them.
Keywords: African Swine Fever; Biosecurity; Gender Roles; Perceptions; Pig Farming; Uganda